Pharmacokinetics and tissue distribution of platinum in rats following single and multiple oral doses of LA-12 [(OC-6-43)-bis(acetato)(1-adamantylamine)amminedichloroplatinum(IV)] - Sova, Petr; Chladek, Jaroslav; Zak, Frantisek; Mistr, Adolf; Kroutil, Ales; Semerad, Martin; Slovak, Zdenek (International journal of pharmaceutics, 2005)
The pharmacokinetics of total and free plasma platinum (Pt) and Pt tissue distribution were investigated in rats after oral administration of (OC-6-43)-bis(acetato)(1-adamantylamine)amminedichloroplatinum(IV) (LA-12). Plasma and ultrafiltrate were sampled until 48 h and tissue samples were taken at 24 and 48 h after single doses of 38.6 or 540 mg LA-12/kg, and after once-a-day dosing of 4.3 or 38.6 mg kg(-1) LA-12 over 14 consecutive days. Total plasma Pt concentrations increased less than proportionally to the 14-fold increase in the single dose. The mean C(max) values of 1.5 and 6.3 mg L(-1) were observed at 0.5 and 1 h, respectively, and the mean AUC values achieved were 29 and 144 mg h L(-1). The highest tissue Pt concentrations were found in the liver and kidneys. Platinum was undetectable in the brain while in other tissues (muscle, skin, heart, lungs), the concentrations were lower (after single dose) or similar (after multiple doses) when compared to the plasma C(max) values. Plasma Pt concentrations after once-a-day dosing of 38.6 mg kg(-1) were two- to three-fold less than that after a single dose while Pt concentrations in various tissues rose two- to four-fold. Accumulation of Pt was even higher in the kidneys (seven-fold) and spleen (nine-fold). After once-a-day dosing, tissue Pt levels increased proportionally with the dose within the range from 4.3 to 38.6 mg kg(-1). At the same time, the increase in total plasma Pt concentrations was 40% less than proportional. Concentrations of Pt in the plasma ultrafiltrate decreased rapidly with the initial half-life of 1 h.
Keywords: tkáňová distribuce; Administration, Oral; krysa rodu Rattus; aplikace orální; platina; Tissue Distribution; Male; Amantadine; Organoplatinum Compounds; Animals; Platinum; Rats, Wistar; mužské pohlaví; amantadin; organoplatinové sloučeniny; potkani Wistar; zvířata; Rats